(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2008)
In order to find out new compounds having antineoplastic activity, bis-tyrosine diaqua nickel (II) complex was synthesized and characterized. The antineoplastic activity of the compound was judged by measuring inhibition of tumour growth and enhancement of survival time of EAC cell bearing mice. In addition its effects on haematological parameters and serum alkaline phosphatase activity of both normal and EAC bearing mice were also studied. The test compound significantly inhibited the tumour growth and increased life span of tumour bearing mice at dose 10 mg/kg i.p. The treatment also recovered the perturbed haematological parameters as well as the serum alkaline phosphatase activity towards normal. The host toxicity of the test compound was found to be negligible. The compound can be considered as an effective antineoplastic agent. Key words: Antineoplastic activity, Bis-tyrosinediaqua nickel (II), EAC, ALP activity Â DOI = 10.3329/dujps.v7i1.1215 Dhaka Univ. J. Pharm. Sci. 7(1): 33-37, 2008 (June)